Volume 1: Codes and Standards 2009
DOI: 10.1115/pvp2009-78103
|View full text |Cite
|
Sign up to set email alerts
|

Microstrucutural Characterization of RPV Steels Irradiated to High Fluences

Abstract: Neutron radiation embrittlement of reactor pressure vessel (RPV) steels is one of critical issues for the structural integrity assessment of the RPVs. Especially, the embrittlement at high fluences is of great interest for the long term operation of light water reactors because information on the mechanical property changes as well as embrittlement mechanisms is limited at high fluences. In this study, microstructural analyses were conducted on the RPV steels irradiated to high fluences in order to confirm the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The data followed the general trend line shown by the dashed line. These results showed that the formation of the solute atom clusters was the main microstructural evolution occurring by the heavy ion irradiations; this has been reported in the same steels irradiated by neutrons [3,14,15]. It was concluded that the microstructural changes similar to those of the neutron irradiation were caused during the heavy ion irradiation.…”
Section: Microstructural Evolutionsupporting
confidence: 70%
“…The data followed the general trend line shown by the dashed line. These results showed that the formation of the solute atom clusters was the main microstructural evolution occurring by the heavy ion irradiations; this has been reported in the same steels irradiated by neutrons [3,14,15]. It was concluded that the microstructural changes similar to those of the neutron irradiation were caused during the heavy ion irradiation.…”
Section: Microstructural Evolutionsupporting
confidence: 70%
“…However, recent microstructural analyses have provided new knowledge mainly from TEM observations and PA measurements. TEM observations with improved specimen preparation techniques using focused ion beam techniques confirmed that dislocation loops are commonly formed in irradiated commercial steels [58,59,77,[98][99][100][101]. Figure 10 shows example TEM images indicating interstitial dislocation loops in A533B steels irradiated with heavy ions [98].…”
Section: Matrix Damagementioning
confidence: 87%
“…However, since the minimum size of the dislocation loops is almost comparable to the resolution limit of TEM (∼1 nm), the reported size and density should be recognized as the values for 'visible' dislocation loops. As the dose increases, the number density shows a clear increase, while the size shows a very slow increase [100].…”
Section: Matrix Damagementioning
confidence: 97%
See 1 more Smart Citation